Comparison of clinical results of Transanal Endorectal Pull-Through of the colon with and without laparoscopic assistance in children with Hirschsprung's disease - V.P. Prytula; O.O. Kurtash; S.F. Hussaini; P.S. Rusak (Group of Companies Med Expert, LLC, Kyev, Ukraine, 2023)
Introduction. Techniques of Transanal Endorectal Pull-Through (TEPT) with and without laparoscopic assistance have been widely used in pediatric surgery for correction of Hirschsprung's disease (HD) in children with. Many clinics in their studies have noted the positive features of this approach compared to classical methods, but the long-term results after such operations in children are still debated. Purpose - to study and compare the clinical results of TEPT with and without laparoscopic assistance in children with HD. Materials and methods. We analyzed the experience of TEPT approach with laparoscopy (n=65 (29.41%)) and without laparoscopic assistance (n=144 (70.59%)) in childreb for correction of HD. For confirmation diagnosis we used the results of general clinical and special procedures (barium enema, anomanometry, histological, determination of acetylcholesterase activity). Results. Overall, among 55 (26.32%) of 209 patients who underwent TEPT, postoperative in long term follow up we found intestinal problems like - moderate stenosis of the colo-anal anastomosis without incontinence 4 (1.91%), constipation 9 (4.31%), partial faecal incontinence 20 (9.57%) and enterocolitis (EC) 22 (10.53%). There was no significant difference in the clinical results of TEPT with laparoscopy and without laparoscopic assistance in our patients. After TEPT without laparoscopic assistance, 6 (4.17%) of 144 patients had constipation, 11 (7.64%) had partial fecal incontinence, and 16 (11.11%) had enterocolitis (EC). And among 65 children after TEPT with laparoscopy, 3 (4.62%) patients were diagnosed with constipation, 9 (13.85%) with partial fecal incontinence and 6 (9.23%) with EC. All children with postoperative intestinal problems were treated conservatively. There was no need for redo surgical interventions in these patients. Conclusions. The technique of TEPT with laparoscopy and without laparoscopic assistance is a modern method of surgical correction of HD, which has significant technical advantages compared to other existing methods. In 26.32% of children with HD who were operated by the TEPT method, persistent intestinal problems continue in the long term follow-up period. The research was carried out in accordance with the principles of the Declaration of Helsinki. The research protocol was approved by the Local Ethics Committee of all institutions mentioned in the work. Informed consent of the children's parents was obtained for the research. No conflict of interests was declared by the authors.